Implementation of Curriculum Integration in The Boarding School Program - Abdullaah Mustaqiim; Mohammad Zakki Azani (JIE (Journal of Islamic Education), 2024)
The purpose of this study is to describe the application of curriculum integration used in the boarding school program at Al-Hadi Islamic Junior High School Sapen, Mojolaban, Sukoharjo, Central Java, Indonesia. This research uses a qualitative method. The research was conducted by observing and interviewing the curriculum section's vice principal at Al-Hadi Islamic Junior High School to collect data; Data analysis techniques are done by data reduction, data presentation, and conclusion drawing; Test the validity of the data by triangulating sources, techniques and time. The results of the study state that the boarding school program at Al-Hadi Islamic Junior High School uses curriculum integration, namely the curriculum of the “Merdeka Belajar” education office and the foundation curriculum. The curriculum integration used aims to balance the achievement of general knowledge with religious knowledge. The main target of this boarding school program is that students are expected to be able to complete memorizing the al-Qur'an 15 juz guided by a musyrif (mentor) and equipped with Arabic language strengthening and the formation of Islamic character values.